Paclitaxel Plus Cetuximab as 1st Line Chemotherapy in Platinum-Based Chemoradiotherapy-Refractory Patients With Squamous Cell Carcinoma of the Head and Neck - Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Ueda, Yuri; Uozumi, Shinya; Tahara, Makoto (Frontiers in Oncology, 2018)
Purpose: We sought to evaluate the efficacy and safety of the combination of cetuximab (Cmab) and paclitaxel (PTX) in patients with squamous cell carcinoma of the head and neck (SCCHN) who had unresectable recurrent or metastatic (R/M) disease after platinum-based chemoradiotherapy. Materials and methods: Data on 23 patients with SCCHN who received paclitaxel and cetuximab (Cmab) for R/M disease no more than 6 months after CRT completion were retrospectively reviewed. PTX and Cmab were given in a 28-day cycle (PTX, 80 mg/m2 on days 1, 8, and 15; Cmab, loading dose 400 mg/m2 followed by a weekly 250 mg/m2). The differences in prognosis between subgroups in different clinical settings were also assessed. Results: CRT had been delivered as definitive treatment in 13 cases (57%) and as adjuvant treatment in 10 (43%). Median time from CRT completion to disease recurrence or metastasis was 73 days (1–152). The best objective response and disease control rates were 52% and 83%, respectively, with 12 partial responses and seven cases of stable disease by Response Evaluation Criteria in Solid Tumors (RECIST). A total of 17 of 23 patients (74%) achieved a degree of tumor shrinkage. Median progression-free survival and overall survival (OS) were 7.0 (95% confidence interval [CI]: 3.7-8.4) and 16.3 months (95% CI: 7.8-23.3), respectively. Patients with a longer duration (≥ 60 d) from CRT completion to disease progression had a statistically significantly longer OS than the others (median OS 22.3 vs. 8.1 months, log-rank test; p = 0.034). Main Grade 3 toxicities included neutropenia (13%), anemia (13%), and hypomagnesemia (13%). No Grade 4 toxicity or treatment-related death was seen. Conclusion: PTX and Cmab is a tolerable and effective option in SCCHN patients with symptomatic CRT-refractory disease. Its favorable effects on tumor shrinkage will help relieve tumor-associated symptoms.